PENERAPAN METODE WEIGHTED AGGREGATED SUM PRODUCT ASSESSMENT (WASPAS) DALAM MENENTUKAN KEDELAI TERBAIK UNTUK PRODUKSI TEMPE (Studi Kasus : Balai Penelitian Tanaman Aneka Kacang dan Umbi) - Miftahul Jannah, Syaputri; Lazulfa, Indana; Widoyoningrum, Sri (Inovate, 2024)
In Indonesia, soybeans are the main source of vegetable protein nutrition. Soybeans are the most important raw material in making tempeh. Tempeh is very popular with the public, besides being affordable, it is also high in vegetable protein. Soybeans have many types and kinds, the many varieties of soybeans make people confused to determine superior soybeans. The purpose of this study is to implement the Weighted Aggregated Sum Product Assessment (WASPAS) method in determining the best soybeans for tempeh production. The criteria used are protein content, fat content, seed color, seed shape and mature age. The system in this study was built using PHP programming language and MySQL as a database processor. The test results of the best soybean recommendation system for tempeh production state that all appearances and functions in the system can be used properly. Based on the calculation results of 8 soybean varieties, the highest value is in the baluran variety with a value of 0.937624224, then there are anjasmoro varieties, burangrang varieties, grobogan varieties, devon 1 varieties, argomulyo varieties, dering varieties 1, and the lowest values are in dena 1 varieties. Keywords: soybean, tempeh, WASPAS method.